Adsorptive removal of chromium(VI) using spherical resorcinol-formaldehyde beads prepared by inverse suspension polymerization - Mulani, Khudbudin; Patil, Vishwanath; Chavan, Nayaku; Donde, Kamini (Journal of Polymer Research, 2019)
The spherical cross-linked beaded polymers were prepared by condensation of resorcinol and formaldehyde in presence of tri-ethylamine by inverse suspension polymerization technique. The m-cresol, aniline, urea and thiourea were used as co-monomer and polyethylene glycol (PEG 400) was used as porogen. Paraffin oil was used as non-aqueous suspension agent. The polymeric spherical beads were prepared using various types of comonomers exhibiting range of particle size 77.62 to 158.84m at 90 degrees C and 300rpm for 4h. The resulting beads were analyzed by elemental analysis, particle size analysis and scanning electron microscope (SEM). The synthesized beads were used for the removal of Cr(VI) from aqueous solutions. A simple and sensitive solid phase extraction procedure was used for the determination of chromium at trace level by spectrophotometric method using 1,5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the resorcinol-formaldehyde beads was monitored by energy-dispersive X-ray spectroscopy (EDX) analysis. The metal adsorption parameters such as contact time, pH, metal ion concentration and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity was about 99% at pH2 for the resorcinol-formaldehyde beads obtained.
Keywords: adsorption kinetics; Beads; Chromium (VI); Formaldehyde; Inverse suspension; Resorcinol